2022
DOI: 10.1024/2673-8627/a000023
|View full text |Cite
|
Sign up to set email alerts
|

Online Identification of Obsessive-Compulsive Symptoms and Relevant Factors in Patients with Covid-19 in Turkey During Quarantine

Abstract: Abstract. Aim: Via online interviews, this study identifies the obsessive-compulsive symptoms (OCSs) of patients diagnosed with Covid-19 and quarantined at home for 14 days, to determine the incidence of these symptoms, to detect OCSs in the early period, and to identify the associated risk factors. Method: This research was designed as a descriptive and cross-sectional study. The study population consisted of patients who had tested positive in the real-time PCR test for Covid-19 and were quarantined at home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…19,20,25,27,30,31,34,37,39,43,46,48 Only three quantitative studies reported adaptive wellbeing outcomes. 31,46,48 Reasons for self-isolation were COVID-19 infection, 21,24,26,28,29,31,33,35,37,40,41,43,45,4749 suspected infection, 42 close contact with an infected person, 30,36,39,52,54 or a combination of these. 19,20,22,23,25,27,32,34,38,44,50,51,53 One study did not report a reason.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…19,20,25,27,30,31,34,37,39,43,46,48 Only three quantitative studies reported adaptive wellbeing outcomes. 31,46,48 Reasons for self-isolation were COVID-19 infection, 21,24,26,28,29,31,33,35,37,40,41,43,45,4749 suspected infection, 42 close contact with an infected person, 30,36,39,52,54 or a combination of these. 19,20,22,23,25,27,32,34,38,44,50,51,53 One study did not report a reason.…”
Section: Resultsmentioning
confidence: 99%
“…In risk of bias assessments, no findings were at low risk, one had some concerns, 35 and most findings were at high, 21,30,32,41,42,44,45,49,51,53 or very high risk of bias. 19,22,29,34,37,40,43,47,54 ; (Appendix 7). Limiting findings to some concerns of bias or high risk of bias did not alter the interpretation of the findings for aim 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…hesaplanmıştır (Tablo 2). Havlioğlu ve arkadaşlarının (26) PE kullanarak karantinadaki hastalara yönelik yaptığı çalışmada %11,2'sinin 82 puan ve üzeri aldığı görülmüştür. Covid 19 pandemi sürecinde obsesif kompülsif belirti görülme sıklıklarını araştıran çalışmalarda; genel popülasyonda %14,5, (1) hamile kadınlarda %31, (9) başka bir yerin genel popülasyonda ise %18 (11) olarak bulunmuştur.…”
Section: Araştırmanın Sınırlılıklarıunclassified